Proppant transport in a scaled vertical planar fracture: Vorticity and dune placement - Fernandez, Matías Ezequiel (2019)
We report experimental results on the transport of proppant in a scaled planar cell. As a complement to many previous studies, we consider, apart from a proper scaling of the experimental cell and flow rate, a scaling of the perforations through which the fracturing slurry is injected. We also consider a fracture height relatively larger than usual, compatible with thick formations such as Vaca Muerta, Neuquén basin (Argentina). Under these conditions, we find that the flow pattern in the fracture presents large vortexes. The effect on the proppant transport is significant, yielding a much deeper placement of the dune than previously observed in similar experiments. We discuss the implications for the design of hydraulic fracturing operations.